EVALUASI PEMILIHAN SUPPLIER BAHAN BAKU TUBE PADA PT AMBER KARYA BATAM - Mustaqim; Susanti, Elva (LPPM Universitas Putera Batam, 2022)
Decision making has become a part of everyday life, and it may be as easy or as complex as you want it to be. In circumstances when a system (simple or complex) is involved, decisions can be made following a preset procedure. For complex situations, the Analytic Hierarchy Process (AHP) may be used to construct a hierarchy of criteria, subjectively appraised by interested parties, and then drawing various considerations to be developed. Priority or heft (conclusion).